Motivation and Job Satisfaction as Predictors of Professional Commitment in Teachers - Vahit Ağa Yıldız (Educational Academic Research, 2024)
In the education process, the person in direct communication with all the stakeholders and the implementer of the process is the teacher. The commitment of teachers to their profession has an important place in achieving the goals of education. As such, it is substantial to specify the variables that are related to and affect it to improve professional commitment. The concepts of teachers' motivation and job satisfaction have occupied a very important place in the literature in recent years. Determining the relationship between these two features and teachers' professional commitment will provide practical benefits for the educational process. The study investigated the relationship between job satisfaction and motivation of teachers with their professional commitment and their effect on it. The research, conducted with a correlational survey design, was carried out with 555 teachers from different school types and branches working in schools in different districts of Erzurum. Data were collected through the Professional Commitment Scale, the Job Satisfaction Scale, and the Teacher Motivation Scale. Multiple Linear Regression Analysis (MLRA) were used to analyze data. The results showed that teachers' professional commitment was positively related on motivation sub-dimensions and job satisfaction. Also, it was designated that job satisfaction and the sub-dimensions of motivation, "professional satisfaction and personal development" and "school management," were significant predictors of professional commitment. Considering the findings and limitations of the study, some suggestions were presented.